Association of serum iron studies in COVID associated mucormycosis with stage of the disease - Rao, Chaitra; V. S., Sheshan; R., Madhumathi; Malagi, Aishwarya D.; B., Vidyasagar (International Journal of Research in Medical Sciences, 2023)
Background: Mucormycosis is a rare and lethal invasive fungal infection caused by opportunist and ubiquitous fungi. India has reported surge in cases of post COVID 19 mucormycosis due to the increasing frequency of risk factors like corticosteroid therapy, uncontrolled diabetes, DKA, neutropenia and iron overload and hence warrants a detailed study to identify potential contributing factors. Aim of this study was to study the clinical profile of patients with CAM and to correlate serum iron studies with severity and extent of disease in CAM patients. Methods: This prospective crosssectional study was conducted on 75 patients with CAM admitted to Bowring Hospital, Bangalore. Detailed history with clinical evaluation and appropriate investigations done and data was analysed. Results: The mean age of the subjects was 48.19 with 52 males and 23 females. Among 75 patients 90.7% were unvaccinated against COVID, 62.7% had oxygen and steroid use, with diabetes mellitus as most common comorbidity. Rhino orbital-cerebral mucormycosis was the most common clinical presentation. Patients with stage 4 CAM had elevated levels of inflammatory markers LDH (292), D-dimer (457), CRP (74.64), mean serum iron (50.37) and TIBC (255.37). Case fatality rate was 12%. Conclusions: The results of this study revealed significant correlation between the clinical severity of CAM and higher mortality, with increased serum iron levels and inflammatory markers. Therefore patients with elevated levels of available serum iron are uniquely susceptible to mucormycosis infection, suggesting dysregulated iron metabolism in its pathogenesis.